(untitled) (GUB Journal of Science and Engineering, 2018)
Early diagnosis of the disease can appreciably improve the survival rate or facilitate effective treatment with different modalities. In the field of disease diagnosis; nanomaterial-based biosensing and bioimaging techniques are lifting hopes for point-of-care cancer diagnosis with ultra-high selectivity and sensitivity. Graphene, including twodimensional (2D) graphene films, three-dimensional (3D) graphene architectures, Graphene dots, and graphene hybrids (GHs) nanostructures have attracted the researcher`s interest in the field of biosensing and bioimaging owing to their properties. Versatile platforms of graphene nanomaterials make it as germane to detect the biomarkers at the early stage of cancer. This review selectively summarizes the recent progress in using graphene-based nanomaterials for detecting lung cancer biomarkers. Explicitly, graphene-electrochemical biosensors, which are classified according to sensing mechanisms and targets (CEA, NSE, hTERT, CYFRA21-1), are thoroughly discussed. Herewith, future scopes and challenges with other matrices, nano-scaffolds have also discoursed in the conclusion and future perspective. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 5(1), Dec 2018 P 51-59